EFEKTIFITAS PENGARUH MODEL PROJECT BASED LEARNING (PJBL) BERBANTUAN MEDIA CANVA TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA KELAS X PADA PEMBELAJARAN PPKN DI SMAS BARRANG LOMPO KOTA MAKASSAR - Anjalita; Abdul Aziz; Akbar Aba (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the persistently low level of students' creative thinking skills in Civics (PPKn) learning. One approach to address this issue is the implementation of a project-based learning model, combined with the use of Canva. This study aims to analyze the effect of the Canva-assisted PjBl model on the creative thinking skills of 10th-grade students at SMAS Barrang Lompo, Makassar City. The study employed a quantitative approach with a quasi-experimental method and a non-equivalent control design. The sample consisted of 33 students, divided into 16 in the experimental class and 17 in the control class. Data were collected through pre- and post-treatment creative thinking tests and student response questionnaires. Data were analyzed using descriptive statistics and independent sample t-tests using the JASP application. The results of the study showed that the average posttest score for students in the experimental class reached 88.50, while the control class obtained an average of 76.88. The results of the hypothesis test showed a significance value of 0.007, which is smaller than 0.05. These findings indicate that the implementation of the Canva-assisted Project Based Learning (PjBL) model has a significant impact on students' creative thinking skills. Furthermore, students showed a positive response to the use of Canva because it increased engagement, creativity, and learning motivation during the learning process. Therefore, the Canva-assisted PjBL model can be an effective learning alternative for developing students' creative thinking skills in Civics (PPKn).